NATO Enlargement: Past And Present Challenges - Methoxha, Inida (Mediterranean Journal of Social Sciences, 2012)
NATO has a solid enlargement experience since its creation in 1949. NATO has undergone 6 rounds of enlargements.NATO enlargement policy during Cold War was oriented to prevent the expansion of communist system in the borders of theWest Europe and ensuring the security of this area. The end of the Cold War had its impact on the European securityarchitecture. The collapse of communism provoked significant changes for the European Security and for the North AtlanticOrganization, which remained the only military and political alliance responsible for the security of Euro Atlantic area. This newsecurity environment naturally poses many questions about the NATO’s transformation and brought into question theenlargement policy of the Alliance. This paper attempts to present the past experience and the present challenges of NATOEnlargement, considering that this process has been very controversial and critical. This current paper concludes that despiteuncertainties, NATO should continue its further expansion, providing strong alliances with a view to enhance the contribution tothe peace and to face with the new challenges arising in the international security environment but maintaining the balance withRussia.